The Berenstain Bears and the giddy grandma - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 1994)
Sister Bear interviews her grandmother for a school assignment, Gran decides to enter her old vaudeville act in the school talent show, and Gramps moves into the gardening shed.
600
600
Accelerated Reader AR
Keywords: Bears -- Juvenile fiction; Schools -- Juvenile fiction; Oral history -- Juvenile fiction; Grandparents -- Juvenile fiction; Talent shows -- Juvenile fiction